The landscape-reclamation results of the Tamariska-hill protected area in Csepel - Gergely, Attila; Tenk, András (JOURNAL OF LANDSCAPE ECOLOGY, 2013)
The Tamariska-hill Protected Area is in the district of Csepel, in Budapest, Hungary. This is a sand hill with several protected plant species that have been under environmental load and are still disturbed by human activity. Beside human impact, the other major problem is the presence of some invasive plants. In 2006, landscape reclamation of the Tamariska-hill by a local NGO began. A botanical survey of the whole area in 2012 confirmed that as the result of landscape reclamation, the number of protected plant species has increased in the territory. The survey has also revealed the appearance of new species, for example that of Eranthis hyemalis and Astragalus asper and confirmed the occurrence of Centaurea arenaria.
Keywords: Budapest; landscape history; sandfield; landscape-reclamation; NGO